Primary extragenital endometrial stromal sarcoma of the lung: first reported case and review of literature - Lara Alessandrini; Francesco Sopracordevole; Giulio Bertola; Simona Scalone; Martina Urbani; Gianmaria Miolo; Tiziana Perin; Fabrizio Italia; Vincenzo Canzonieri (BMC, 2017)
Abstract Background Endometrial stromal sarcomas arising in extrauterine and extraovarian sites, in the absence of a primary uterine lesion are quite rare, especially in the absence of endometriosis. They usually present as an abdominal or pelvic mass lesion. Case presentation In 2007, a 45-year-old woman underwent total hysterectomy for in situ squamous cell carcinoma of the cervix. In 2014, an upper left pulmonary lobectomy was performed for a mass, which was provisionally diagnosed as primary carcinosarcoma of the lung. A second histological revision of the lung surgical specimen was performed in the Pathology Unit of our Institute. After extensive immunohistochemical analyses, the preferred diagnosis was spindle-cell sarcoma, consistent with high-grade extragenital endometrial stromal sarcoma (EESS). A review of all slides of the hysterectomy specimen confirms the original diagnosis: no evidence of stromal tumor was found. Afterwards, the patient developed multiple and metachronous pulmonary lesions and a scapular soft tissue mass, which showed the same morphophenotypic features of the first lung mass. The patient was treated with antiblastic therapy, surgical resection and radioablation, when appropriate. To date, the patient has no signs or symptoms. Conclusions The authors present the first case of primary EESS arising in the lung with no association with endometriosis published to date. Detailed clinical history and follow-up are also described. Moreover, extensive literature review is reported, along with differential diagnoses, immunohistochemical and molecular findings, pathogenetic hypotheses and treatment options. The knowledge of EESS potential extrauterine location and of its peculiar morphophenotypic aspects are required for a correct diagnosis, and for choosing the most suitable treatment.